2017
DOI: 10.18632/oncotarget.20883
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of microRNAs in hepatocellular carcinoma: a meta-analysis

Abstract: BackgroundNumerous articles reported that dysregulated expression levels of miRNAs correlated with survival time of HCC patients. However, there has not been a comprehensive meta-analysis to evaluate the accurate prognostic value of miRNAs in HCC.DesignMeta-analysis.Materials and MethodsStudies, published in English, estimating expression levels of miRNAs with any survival curves in HCC were identified up until 15 April, 2017 by performing online searches in PubMed, EMBASE, Web of Science and Cochrane Database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 217 publications
1
25
0
Order By: Relevance
“…These results are consistent with previous reports. 7 28 35 36 By dual luciferase reporter assay and examining XIST expression status in XIST overexpressing HepG2 cells transfected with miR-155-5p mimic, we identified XIST as a direct target of miR-155-5p, and overexpressing XIST was able to partially rescue the protein expression levels of some HCC suppressing genes previously identified as direct targets of miR-155-5p in miR-155-5p mimic-transfected HepG2 cells, including PTEN and SOX6. 16 18 37 The HCC suppressing role of XIST antagonizing that of miR-155-5p was further revealed by cell functional assays: XIST overexpression not only decreased cell proliferation while increasing apoptosis, but also increased the susceptibility of HepG2 cells to cisplatin treatment, which was undermined by miR-155-5p mimic transfection.…”
Section: Discussionmentioning
confidence: 86%
“…These results are consistent with previous reports. 7 28 35 36 By dual luciferase reporter assay and examining XIST expression status in XIST overexpressing HepG2 cells transfected with miR-155-5p mimic, we identified XIST as a direct target of miR-155-5p, and overexpressing XIST was able to partially rescue the protein expression levels of some HCC suppressing genes previously identified as direct targets of miR-155-5p in miR-155-5p mimic-transfected HepG2 cells, including PTEN and SOX6. 16 18 37 The HCC suppressing role of XIST antagonizing that of miR-155-5p was further revealed by cell functional assays: XIST overexpression not only decreased cell proliferation while increasing apoptosis, but also increased the susceptibility of HepG2 cells to cisplatin treatment, which was undermined by miR-155-5p mimic transfection.…”
Section: Discussionmentioning
confidence: 86%
“…Their results suggest that circulating miR-221 expression could be a prognostic marker. In a large screening study, Zhang et al [97] investigated the potential prognostic miRNAs using data from 54 relevant articles and 6464 patients and identified circulating miR-148a and miR-192 as reliable prognostic markers in HCC. Jin et al [87] also revealed that six miRNAs (miR-424-5p, miR-101-3p, miR-128, miR-139-5p, miR-382-5p, and miR-410) were significantly related with overall survival rate in 116 HCC patients and had potential to be good biomarkers for predicting prognosis.…”
Section: Body Fluid Case Number Control/number Micrornas Regulationmentioning
confidence: 99%
“…It is clear that miRNA plays a role in proliferation, persistence, invasion, metastasis, and prognostic indicators of hepatocellular carcinoma [ 36 39 ]. In liver cancer tissue, there are many abnormally expressed miRNAs, such as miR-224, miR-221, and miR-21 that influence hepatocellular carcinoma [ 40 42 ]. miR-224 has been shown to target HOXD10 RNA and enhance both PAK4-mediated phosphorylation and MMP-9 to promote the invasion and metastasis of cancer cells [ 43 ].…”
Section: Abnormal Expression Mirnas In Hccs and Serum Of Patients mentioning
confidence: 99%